Manajemen Sarana dan Prasarana Pendidikan (Studi Kasus SMA Negeri 2 Lubuk Sikaping) - Juita, Dince Putri; Mestika, Yonia; Kurnia, Dela; Asmendri, Asmendri; Sari, Milya (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The purpose of writing this article is to find out how the management and management of high school educational facilities and infrastructure at SMA Negeri 2 Lubuk Sikaping. Facilities and infrastructure greatly affect the ability, comfort, and activeness of students in learning. This shows that the role of facilities and infrastructure plays an important role in supporting the quality of student learning. The methods used in this study are qualitative methods with a descriptive approach, and research data based on field observations, interviews, and documentation studies. The research finding is that SMA Negeri 2 Lubuk Sikaping already has the facilities and infrastructure required in Permendikbudristek No.22 of 2023 concerning Facilities and Infrastructure Standards, but in the management of facilities and infrastructure has not applied modern management principles which include the functions of planning, procurement, inventory, storage, distribution, maintenance, elimination as well as assessment and supervision. Management of facilities and infrastructure is an important activity carried out by schools because these facilities and infrastructure greatly support the success of the learning process in schools